Table S6, Biomarker isotopic data of crenarchaeol (δ13C Cren.), bacteriohopanetetrol I (δ13C BHT-I), and bacteriohopanetetrol II (δ13C BHT-II) for ODP cores at sites 964 and 967 - Felix J Elling; Jordon D Hemingway; Jenan Kharbush; Kevin W Becker; Catherine Ann Polik; Ann Pearson (PANGAEA, 2021)
Stable-carbon isotope compositions for crenarchaeol, bacteriohopanetetrol I (BHT-I), and bacteriohopanetetrol II (BHT-II) for ODP cores at sites 964 and 967. All biomarkers were measured using a Thermo Scientific Delta V isotope ratio mass spectrometer at least in triplicate. For BHT-I and BHT-II, compounds were isolated using high-performance preparative liquid chromatography and individually analyzed by high-temperature gas-chromatography-IRMS following Hemingway et al. (2018). Crenarchaeol was isolated using high-pressure preparative chromatography and analyzed using a spooling-wire microcombustion interface on a Thermo Scientific Delta V isotope ratio mass spectrometer at least in quintuplicate following Polik et al. (2018). This work was supported by the Gordon and Betty Moore Foundation.
In: Elling, FJ et al. (2021): Mediterranean sapropel bulk organic matter and biomarker concentrations and carbon isotope compositions [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.937082